2015
DOI: 10.4103/0970-9290.159152
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of shear bond strength of nano-hydroxyapatite incorporated glass ionomer cement and conventional glass ionomer cement on dense synthetic hydroxyapatite disk: An in vitro study

Abstract: The lower shear bond strength of nano-HAp incorporate GIC revealed that the addition of nano-HAp interfered with the bonding ability of GIC to the substrate interface, but the mixed type of failure in nano-HAp incorporated GIC suggests that it increases the strength of the matrix. However, the role of nano-size particles on the micro-size particles of GIC for the bonding mechanism and the ratio and proportions of nano-HAp to the GIC needs further elucidation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 0 publications
0
7
1
Order By: Relevance
“…Since HA has excellent biocompatibility and similarity in crystal structure to that of apatite in human dental and skeletal systems, a number of studies have been carried out to study the effect of addition of HA powder to dental restorative materials. Incorporation of HA particles have led to significant improvement of mechanical properties such as compressive, diametral tensile strength and shear bond strength of GICs [9,10]. HA granules exposed on the surface of GIC could facilitate bioactive reaction involving formation of carboxylate groups in the polyacid [11].…”
Section: Introductionmentioning
confidence: 99%
“…Since HA has excellent biocompatibility and similarity in crystal structure to that of apatite in human dental and skeletal systems, a number of studies have been carried out to study the effect of addition of HA powder to dental restorative materials. Incorporation of HA particles have led to significant improvement of mechanical properties such as compressive, diametral tensile strength and shear bond strength of GICs [9,10]. HA granules exposed on the surface of GIC could facilitate bioactive reaction involving formation of carboxylate groups in the polyacid [11].…”
Section: Introductionmentioning
confidence: 99%
“…Similar results were found in the study conducted by Choudhary K (2015). 9 The mean shear bond strength values obtained for nano-HAp incorporated GIC (3.98 ± 0.23 MPa) was lower to the value obtained from study by Moshaverinia et al 10 In this study, intra-oral variables such as normal masticatory stress, moisture, intra-pulpal pressure, and operator inconsistencies were not taken into consideration. Therefore, further in vivo studies are necessary to test the long-term stability of these materials.…”
Section: Materials and Method:-contrasting
confidence: 38%
“…Although polyacrylic acid (PAA) was not used conventionally in the intraradicular space, it was included in this study, considering its indication in dentin conditioning to potentiate adhesiveness [ 28 29 ]. The results showed that PAA was less effective than EDTA in removing the smear layer.…”
Section: Discussionmentioning
confidence: 99%
“…However, PAA was used for 20 seconds in this study, according to the manufacturer's recommendations for restorations with glass ionomer cement. Therefore, we believe that further studies are needed to analyze the removal of the smear layer using the PAA for a longer period, considering that root dentin is more mineralized and sclerotic than the coronary dentin [ 31 32 ], for which this material has presented satisfactory results [ 28 29 ].…”
Section: Discussionmentioning
confidence: 99%